Stability Evaluation of Candlenut Oil Capsule: Disintegration, Iodine Value, Omega Content, and Drug Kinetics - Hery Sutanto; Wulan Sutardiman; Silvya Yusri (Sanata Dharma University, 2023)
Candlenut oil, known for its high omega-3 fatty acid content (up to 90%), shows great promise as a valuable source of omega. However, its rich unsaturated fatty acid composition makes it susceptible to oxidation and quality degradation. To address this, candlenut oil is encapsulated for use as a food supplement product. This research aims to investigate the stability of omega oil content in capsulated candlenut oil as well as the physical and chemical properties of gelatin and seaweed-based hard capsules used for encapsulation. Additionally, the study explores the optimal capsule material, opacity, and storage conditions for preserving the quality of candlenut oil products. Three key factors were considered: capsule material (gelatin and seaweed-based), capsule opacity (colored and transparent), and storage temperature (cool temperature with relative humidity of 33% and ±8°C, or room temperature with relative humidity of 65% and ±28°C). The evaluation of the best capsule material and optimum storing temperature of candlenut oil capsules was based on disintegration time, iodine value analysis, and omega content analysis. The results indicate that the disintegration times for gelatin and seaweed capsules were 5.80 and 5.78 minutes, respectively. Transparent gelatin capsules demonstrated the best performance in preventing oil quality degradation, as confirmed by the iodine value analysis. Both gelatin and seaweed capsules exhibited the ability to prevent the degradation of omega oil when stored at cool temperatures, with an estimated kinetic shelf life of 2.92 years.